Factors associated with methicillin-resistant coagulase-negative staphylococci as causing organisms in deep sternal wound infections after cardiac surgery. (July 2015) - Sommerstein, R.; Kohler, P.; Wilhelm, M.J.; Kuster, S.P.; Sax, H.
Abstract: Established preoperative antibiotic prophylaxis in cardiac surgery is ineffective against methicillin-resistant coagulase-negative staphylococci (CoNS). This case–control study aimed to determine factors predicting deep sternal wound infections due to methicillin-resistant CoNS. All cardiac surgery patients undergoing sternotomy between June 2009 and March 2013 prospectively documented in a Swiss tertiary care center were included. Among 1999 patients, 82 (4.1%) developed deep sternal wound infection. CoNS were causal in 36 (44%) patients, with 25/36 (69%) being methicillin resistant. Early reintervention for noninfectious causes (odds ratio (OR) 4.3; 95% confidence interval (CI) 1.9–9.5) was associated with methicillin-resistant CoNS deep sternal wound infection. Among CoNS deep sternal wound infection, perioperative antimicrobial therapy (p 0.002), early reintervention for noninfectious causes (OR 7.9; 95% CI 0.9–71.1) and time between surgery and diagnosis of infection over 21 days (OR 10.8; 95% CI 1.2–97.8) were associated with methicillin resistance. These findings may help to better tailor preoperative antimicrobial prophylaxis.